Peran Penyidik Harta Benda Dalam Rangka Menangani Pelaku Tindak Pidana Pemalsuan SuratGuna Terwujudnya Kepastian Hukum di Kepolisian Daerah Daerah Istimewa Yogyakarta - Suranto Suranto; Lilik Mulyadi; Suryawan Raharjo (Kajian Hasil Penelitian Hukum, 2019)
This study aims to determine the role of investigator Harda Polda DIY in dealing with fraudulent offenders, because of letter forgery cases this results in material losses and immaterial Knowing the impact of the active role generated from the investigation of the DIY Regional Police Harda Subdistrict against the perpetrators of letter forgery, so that the legal process obtained legal certainty for both victims and perpetrators of falsification of letters, in addition to knowing thecausal factors the occurrence of falsification of the letter and knowing the steps of Investigator Harda in dealing with the perpetrators of criminal acts of letter forgery. The approach used by the author is an empirical juridical approach, namely the approach of existing law to be applied in cases that occur, namely analyzing how the role of Investigator Harda against criminal acts of forgery of letters carried out by perpetrators in the jurisdiction of the Regional Police of DIY. The analysis used is qualitative, namely the method of data analysis by grouping and selecting data obtained from research according to the quality and truth, then connected with the theories from the literature study. The investigator in determining the role taken against the perpetrators of the crime of forgery of letters is by knowing the factors that cause the occurrence of letter forgery, this step is based on Article 13 of Law Number 2 Year 2002 concerning the National Police of the Republic of Indonesia and Perkap Number 10 Year 2010 Regulation of the Chief of Police However, in the process of investigating Harda investigators, it did not provide a deterrent effect on the perpetrators of not carrying out similar actions, this was because the investigation process was still not maximal, so many perpetrators of criminal acts of letter forgery still escaped legal entrapment. Law enforcement activities carried out by Investigator Harda are always improving Capability, Awareness, Attitude and Behavior so that legal certainty can be achieved for both victims and perpetrators of fraudulent letters.